Hubungan Antara Minat Bekerja di Industri Dengan Prestasi Belajar Praktek Kerja Industri (Prakerin) Pada Siswa Kelas Xi Jurusan Teknik Gambar Bangunan Tahun Akademik 2011/2012 SMK NEGERI 35 JAKARTA - Ristiani, Tia Anjar (Jurnal Pensil : Pendidikan Teknik Sipil, 2014)
This study aims to determine the relationship between interest in working in the industry with industry practice learning achievement (prakerin) in class XI jurusa drawing technique building academic year 2011/2012 SMK Negeri 35 Jakarta. The study lasted for 3 months from August to November 2013. The place of research conducted at SMK Negeri 35 Jakarta. The population in this study were students of class XI academic year 2011/2012 majoring in engineering drawings are 39 people. The method used in this study is a method of filling a questionnaire survey to obtain primary data for the variables X and secondary data from prakerin value for the variable Y, the approach used is correlational approach. Trial questionnaire instrument conducted by 10 respondents majoring in engineering drawing class XI buildings. After the test phase results obtained valid instrument for data collection on a sample, the number of items valid statement after test instruments is 40 statement items. Data analysis techniques starts with finding the simple linear regression equation Å¶ = 93,64 + (- 0,062 X). While testing requirements analysis is to test the normality of the estimated regression error Y over X with Liliefors test produces a maximum of 0,1057 whereas Lcount, Ltable on stage at significance level (Î±) of 0,05 obtained a value of 0,1418 then obtained Lcount <Ltable or 0,1057 < 0,1418 thus it can be concluded that the estimated regression error Y over X is normally distributed. Linearity of regression test yield of Fcount = 1,45 while the Ftable = 2,72, then the results show that the Fcount < Ftable which means the linear regression, followed by testing the significance of regression produces that (Fcount = 0,789) < (Ftable = 4,11) so the regression by no means. The results of calculations conclude that there is negative relationship between the Interests Working in the Industry Achievement Industry Practice.